Psychological wellbeing and health-related quality of life in children and adolescents : focus group methodology - Gaspar, Tânia, 1977- (2012)
The present study has the main objective to characterize the psychological factors that influenced Health-Related Quality of Life (HRQoL) in Portuguese children and adolescents attending the 5th grade and 7th grade from public schools, and to analyze the HRQoL by gender, age and socioeconomic status (SES). The HRQoL will be assessed by analyzing the children's and the adolescents' perception of their own HRQoL, by considering the parents' perception of their children's HRQoL and finally by considering the education professionals' perception of children' and adolescents' HRQoL. Was used a qualitative methodology and focus groups as methodology. The sample included 53 children and adolescents with ages between 10 and 15 years old, 36 parents, 34 teachers and 17 educational assistants. 16 focus groups were developed. An interview guide was elaborated for the focus groups. The results of this research identified the HRQoL risk groups, namely girls, adolescents (the older group) and pupils with low SES. The results revealed that the HRQoL in children and adolescents is influenced by physic health factors, psychological and social factors and by health behaviours. However psychological factors demonstrated a higher effect, either regarding a direct or indirect impact, in the HRQoL of children and adolescents. Were present suggestions and implications for HRQoL intervention and promotion, regarding an ecological and developmental approach. (Tânia Gaspar... [et al.])